INCREASED EFFICIENCY OF BALL MILL RUBBER LININGS IN CONSTRUCTION MATERIAL PRODUCTION - Gennady Petrovich Sheludko; Valery Mikhailovich Goncharov; Savva Viktorovich Skorikov (Вестник Северо-Кавказского федерального университета)
The article provides a view on the newly developed heat-resistant rubber lining for mill balls employed under dry milling at higher temperatures (up to 140 - 160 оС). There have been comparative industrial trials carried out to test the heat-resistant and steel lining, and its advantages have been shown. There is also a view on the efficiency and the potential future production of rubber lining for ball mills employed to grind abrasive materials.